Hydroacoustic and Sediment data collected during AL-519/1 in January 2019 in the German Bight - Finn Mielck; Werner Armonies (PANGAEA, 2021)
During the research cruise AL-519-1 with RV Alkor the effects of dredging measures in an extraction site west off Sylt (German Bight) were investigated. Here, sandy material was extracted since 1984 for beach nourishment on the Island of Sylt. The extraction site lies approx. 7 km west of Sylt and has an extend of 5.5 km*3 km with water depths between 13 and 32 m. The investigations took place in January 2019 and lasted about five days. In order to assess the morphology of the study site, a gapless bathymetry was measured using a multibeam echosounder (ELAC Seabeam 1000, 180 kHz). For the determination of further seafloor characteristics and backscatter responses of the seafloor, a sidescan sonar were used (Imagenex YellowFin 872, 330 kHz). In addition, 55 sediment samples were taken in different domains of the study site (e.g. old dredging pits, new dredging pits, unaffected seafloor). The sediment samples were examined with regard to their grain sizes as well as their macrozoobenthos community composition.